2017
DOI: 10.1189/jlb.3ma0117-025r
|View full text |Cite
|
Sign up to set email alerts
|

Can we design a better anti-cytokine therapy?

Abstract: Cytokine neutralization is successfully used for treatment of various autoimmune diseases and chronic inflammatory conditions. The complex biology of the two well-characterized proinflammatory cytokines TNF and IL-6 implicates unavoidable consequences when it comes to their global blockade. Because systemic cytokine ablation may result in unwanted side effects, efforts have been made to develop more specific cytokine inhibitors, which would spare the protective immunoregulatory functions of a given cytokine. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 92 publications
0
33
0
2
Order By: Relevance
“…IL-6 binds to the IL-6 receptor (IL-6R), which exists both in membrane-bound and soluble forms (sIL-6R). IL-6 binding involves both gp130 and sIL-6R, and the IL-6/sIL-6R/ gp130 complex mediates downstream signaling and activation of the JAK-STAT pathway [119]. Studies have demonstrated that the deleterious effects of IL-6 almost exclusively involve sIL-6R, whereas the membranebound form protects against infections and is involved in tissue regeneration [119,122].…”
Section: The Future Of Cytokine Adsorption Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…IL-6 binds to the IL-6 receptor (IL-6R), which exists both in membrane-bound and soluble forms (sIL-6R). IL-6 binding involves both gp130 and sIL-6R, and the IL-6/sIL-6R/ gp130 complex mediates downstream signaling and activation of the JAK-STAT pathway [119]. Studies have demonstrated that the deleterious effects of IL-6 almost exclusively involve sIL-6R, whereas the membranebound form protects against infections and is involved in tissue regeneration [119,122].…”
Section: The Future Of Cytokine Adsorption Therapymentioning
confidence: 99%
“…Most of the proinflammatory actions of TNF are believed to be mediated by TNF receptor-1. The roles of the TNF receptor-2, while incompletely understood [119], may include the resolution of inflammation [124,125], tissue regeneration, neuroprotection [126], and suppression of cytotoxic T-cell populations that cause type 1 diabetes mellitus [127]. Removal of serum TNF may compromise signaling through this receptor, thus abrogating these physiologic functions.…”
Section: The Future Of Cytokine Adsorption Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…4. Structural scheme of bi-specific antibodies, recognizing hTNF and mouse myeloid cell surface molecules (F4/80 and CD11b), as well as the control construct, binding hTNF, but not any of the surface molecules of murine macrophages Следующим шагом должна стать разработка прототипов лекарств, которые по тому же принципу могли бы взаимодействовать с маркерами миелоидных клеток человека [15]. К сожалению, наша фармацевтическая промышленность сконцентрирована на аналогах уже разработанных и одобренных зарубежных лекарств и пока не заинтересована в развитии проектов, которые неизбежно сопряжены с рисками.…”
Section: фармакологическая блокировка Tnf продуцируемого миелоиднымиunclassified